Preserved speed of processing and memory in infants with a history of moderate neonatal encephalopathy treated with therapeutic hypothermia. (December 2018) - Zorn, Elizabeth; Zhang, Lei; Sandness, Kristin; Miller, Neely; Riggins, Tracy; Georgieff, Michael; Pfister, Katie
Abstract Objective: Survivors of neonatal encephalopathy (NE) are at risk for impaired cognition. The objective of this study was to assess speed of processing (SOP) and memory in infants with moderate NE. Study design: Sample consisted of 17 infants with NE and 23 healthy controls. Visual-evoked potentials (VEP) were assessed at 8 months to assess SOP. Memory was assessed at 12 months using elicited imitation (EI). Memory and SOP had previously been assessed in this cohort in the newborn period. Results: Infants with NE had similar SOP and EI performance as controls. Newborn SOP correlated with 8-month SOP in infants with NE, however, neonatal ERP memory measures were not correlated with EI performance at 12 months. Conclusions: Infants with moderate NE treated with TH show preserved memory and SOP through 12 months. Early behavioral and electrophysiologic assessments of memory and SOP provide insight into developing cognitive functions in this risk group.